2007
DOI: 10.2307/25065911
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and temporal diversification of western European polyploid species complexes in Dactylorhiza (Orchidaceae)

Abstract: Patterns of polyploid evolution in the taxonomically controversial Dactylorhiza incarnata/maculata groups were inferred genetically by analyzing 399 individuals from 177 localities for (1) four polymorphic plastid regions yielding aggregate haplotypes and (2) nuclear ribosomal ITS allele frequencies. Concordance between patterns observed in distributions of plastid haplotypes and ITS alleles renders ancestral polymorphism an unlikely cause of genetic variation in diploids and allopolyploids. Combining the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
226
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(244 citation statements)
references
References 52 publications
18
226
0
Order By: Relevance
“…Analysis of a sample of Dactylorhiza iberica collected in the Pindos Mountains of northern Greece was conducted too late for its inclusion in the published tree; the authors simply reported in the text its position as near-basal within the genus. Identical topologies, differing only in bootstrap support values, were later produced from ITS matrices by Pillon et al (2007), Tang et al (2015) and Bateman et al (in review).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of a sample of Dactylorhiza iberica collected in the Pindos Mountains of northern Greece was conducted too late for its inclusion in the published tree; the authors simply reported in the text its position as near-basal within the genus. Identical topologies, differing only in bootstrap support values, were later produced from ITS matrices by Pillon et al (2007), Tang et al (2015) and Bateman et al (in review).…”
Section: Discussionmentioning
confidence: 99%
“…A year later, Pillon et al (2007, their Appendix 1) published a considerably expanded dataset that included ten geographically disparate samples of Dactylorhiza viridis and two samples of D. iberica; sample 960 from Cyprus was finally joined by sample "Hedrén 98078" from northwest Turkey. Nonetheless, sample 960 -presumably by now re-sequenced -was once again selected to represent D. iberica in their ITS tree.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations